Operating Principles and Applications of Blockchain Technology (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This study is intended for independent users and students, all users of the blockchain form a network of computers, each of which has copies of data blocks. Usually full copies of all these blocks are stored in the required blocks. Therefore, the data in the blockchain blocks cannot be hacked, destroyed, processed, because the data on all computers must be deleted or changed. Blockchain has the following advantages: each new user expands this system and increases its tolerance; since the blockchain system is decentralized, there is no central administrator in the system; all users manage their blocks and have the ability to delete entries in blocks.